(untitled) (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2021)
The interviews were transcribed and later entered into a qualitative software program (Nvivo) for this was a qualitative exploratory study that intended to explore the differences between school social worker and the school counselor. It aims to determine the perceptions of school social workers. This study also intends to determine the role of social workers in schools and the services they could provide for the students. A semi-structured interview was developed by the researchers. Subjects were interviewed using a semi-structured process. The basic questions for this study were: Is there need for school social workers? What are the roles of school social workers? What are the differences between the counselor and the school social worker? What are the common problems in schools that require a school social worker? Overall findings from the three groups indicated that school social workers have multiple roles, including intervention and integrating students with their classmates in the school, especially those who come from different groups like refugees. Also, their roles based on the participants’ perspective involve linking the school with the resources in the community. Moreover, the role involves cooperation with all members in the school to solve students’ problems and improve their academic achievement. Also, participants indicated that there could be differences between the school social workers and counselors based on their roles since the social worker role is deeper and more comprehensive for the students’ issues than the counselor. Some indicated there is no difference between the two roles while some did not recognize that a member in the school was called the school social worker. In summary, the problems that require a school social worker are many but the same in most schools. The basic problems are dropouts, drug use and smoking, low academic achievement, and behavioral and emotional problems. The challenges and barriers that limit the existence of school social workers in the Jordanian community are many. All three groups agreed that policymakers did not pay attention to the importance of school social workers because of the economic factor. Most participants agreed that our culture has been changed and developed, and that parents nowadays are more aware of their children’s school problems and they need someone professional to help deal with these problems.